The Dean in The Church of Norway: From the bishop's helper to independent middle manager in The Church of Norway (Nordic Journal of Practical Theology, 2023)
The office of dean (prost) in the Church of Norway has been a constant and important factor in the development of congregational life. It was designed already in the Church legislation of the Reformation as a regional supervisor of parishes and pastors, and as assistant to the bishop. The dean was elected by clergy in the relevant area and confirmed by the local and the King’s local representative. The dean’s tasks were mainly oversight over local pastoral work, catechetical instruction, and church building maintenance. The dean was expected to visit the parishes regularly and report to the bishop. During the previous century, following a renewal of congregational life and new challenges from a changing world and a disintegrated society, new patterns of leadership emerged, which also affected the church. The outcome has been a new model of pastoral leadership, with the office of dean designed in categories from general leadership theories, functioning as an independent leader between bishop and local church level.
Keywords: Church order; Pastoral theology; Visitation; Order of ministry; Leadership; Dean